Media as a space of aggression (Eurasian Journal of Philology Science and Education, 2016)
This article discusses different classifications of verbal aggression in various spheres of human activity. The author pays attention to the fact that speech aggression has many functions being a means of influencing the recipient; manifestation of the desire to inflict pain; demonstration of the desire to subjugate anyone; means of expressing power, superiority, the language of violence, etc. The article identifies and describes the most common forms of verbal aggression in the media. Verbal aggression can vary in intensity and forms of its manifestations: from expressing resentment and hostility to verbal abuse.
Keywords: Media; aggression; verbal aggression; insult; mockery; reproach; threat; irony; sarcasm.